Monitoring blood flow responses during topical ALA-PDT - Becker, Theresa L. (Optical Society of America, 2010)
Photodynamic therapy (PDT) using topical 5-aminolevulinic acid (ALA) is currently used as a clinical treatment for nonmelanoma skin cancers. In order to optimize PDT treatment, vascular disruption early in treatment must be identified and prevented. We present blood flow responses to topical ALA-PDT in a preclinical model and basal cell carcinoma patients assessed by diffuse correlation spectroscopy (DCS). Our results show that ALA-PDT induced early blood flow changes and these changes were irradiance dependent. It is clear that there exists considerable variation in the blood flow responses in patients from lesion to lesion. Monitoring blood flow parameter may be useful for assessing ALA-PDT response and planning.